إعادة بناء تصميم مكونات منهج اللغة العربية في مدرسة التربية الإسلامية بشاندونج، سومطرة الغربية – إندونيسيا: دراسة ميدانية تحليلية - Mardi, Isra; Syafei, Isop (Al-Fakkaar, 2026)
This study aims to examine and reconstruct the design of the core components of the Arabic language curriculum at Madrasah al-Tarbiyah al-Islamiyah Shandong, West Sumatra, Indonesia, through a critical and applied approach grounded in field-based research. The study focuses on four main curriculum components: learning objectives, instructional content or materials, teaching methods and strategies, and the assessment system. Employing a qualitative research design, data were collected through direct classroom observations, semi-structured interviews with teachers and school administrators, and questionnaires administered to students in order to obtain more comprehensive and contextualized insights into the actual implementation of the curriculum. The findings reveal that the Arabic language curriculum implemented at the school remains largely dominated by traditional approaches, particularly in the formulation of learning objectives, the selection of instructional content, teaching strategies, and assessment practices. As a result, the curriculum is less responsive to the demands of 21st-century competencies. Accordingly, this study emphasizes the need to reconstruct the curriculum design to be more communicative, contextual, and integrative with educational technology, while also being responsive to learners’ needs and learning environments. The study recommends adopting a competency-based curriculum model that incorporates the communicative approach, thematic orientation, collaborative learning, and authentic assessment as key foundations for renewing Arabic language education in contemporary Islamic educational institutions